Numerical Design of Ultra-Wideband Printed Antenna for Surface Penetrating Radar Application - Roy B. V. B. Simorangkir; Achmad Munir (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2011)
Surface penetrating radar (SPR) is an imaging device of electromagnetic wave that works by emitting and transmitting a narrow period pulse through the antenna. Due to the use of narrow period pulse, according to the Fourier transform duality, therefore ultra-wideband (UWB) antenna becomes one of the most important needs in SPR system. In this paper, a novel UWB printed antenna is proposed to be used for SPR application. Basically, the proposed antenna is developed from a rectangular microstrip antenna fed by symmetric T-shaped. Some investigation methods such as resistive loading, abrupt transition, and ground plane modification are attempted to achieve required characteristics of bandwidth, radiation efficiency, and compactness needed by the system. To obtain the optimum design, the characteristics of proposed antenna are numerically investigated through the physical parameters of antenna. It is shown that proposed antenna deployed on an FR-4 Epoxy substrate with permittivity of 4.3 and thickness of 1.6mm has a compact size of 72.8mm x 60.0mm and a large bandwidth of 50MHz-5GHz which is suitable for SPR application.